Superorder Parasitiformes Reuter, 1909. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Beaulieu, Frédéric; Dowling, Ashley P. G.; Klompen, Hans; de Moraes, Gilberto J.; Walter, David Evans (Zootaxa, 2011)
-